Macroeconomic Conditions and Import Surcharges in Selected Transition Economies - Sorsa, Piritta (IMF Working Papers; Working Paper, 1999)
Analysis on macroeconomic determinants of protection in the Czech and Slovak Republics, Hungary, and Poland, while subject to many caveats, suggests that appreciation of the real exchange rate was the main macroeconomic determinant of trade policy reversals in the 1990s. This suggests that balance of payments difficulties may have been used as an excuse for protection. The analysis also suggests that greater exchange rate flexibility and tighter fiscal policies could have been used instead of import surcharges to deal with external imbalances. The surcharges may only have aggravated the external balance by slowing down exports and restructuring of production.